Pengaruh Larutan Hara dan Eco Enzyme terhadap Pertumbuhan Sawi Hijau (Brassica juncea L.) pada Sistem Hidroponik - Jasmine, Nataya Annisa; Rachmawati, Diah (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Limited agricultural land has caused a decline in the productivity of green mustard (Brassica juncea L.) as one of the nutritious vegetables that is widely consumed by the public. Cultivating vegetables using a hydroponic wick system is a solution to increase the productivity of green mustard. The expensive price of nutrient solutions can be combined with eco enzymes as a provider of essential nutrients for plants. This research aims to determine the effect of the combination of AB mix with eco enzyme on the growth of green mustard. The research was designed with RAL, 8 treatments, and 3 replications. Treatments include A1E0=AB mix 100%+0mL/L eco enzyme, A1E1=AB mix 100%+1mL/L eco enzyme, A1E2=AB mix 100%+2mL/L eco enzyme, A1E3=AB mix 100%+3mL eco enzyme, A2E0=AB mix 75%+0mL eco enzyme, A2E1=AB mix 75%+1mL/L eco enzyme, A2E2=AB mix 75%+2mL/L eco enzyme, and A2E3=AB mix 75%+3mL/L eco enzyme. The parameters measured were plant height, number of leaves, wet weight of roots and shoots, dry weight of roots and shoots, and leaf area. Data were analyzed using analysis of variance and DMRT testing with Î±=0.05. The combination of AB mix with eco enzyme had no effect on plant height, number and area of leaves, and wet weight of roots and shoots. However, the highest dry weight of roots and shoots in the A2E2 treatment showed significantly different results from the control treatment (A2E0). Eco enzymes act as nutrient substitutes which are influenced by sunlight, plant metabolism and water absorption capacity.